The mechanism of the dose effect of straw on soil respiration: Evidence from enzymatic stoichiometry and functional genes - Li, Shuailin; Cui, Yongxing; Xia, Zhuqing; Zhang, Xinhui; Zhu, Mengmeng; Gao, Yun; An, Siyu; Yu, Wantai; Ma, Qiang (Soil biology & biochemistry, 2022)
Straw return to soil is a global field practice for sequestering carbon (C) in agricultural ecosystems, and soil C mineralization depends on the soil microbial metabolic process. However, the variation patterns of microbial respiration (Rs) and associated mechanisms under long-term straw input at different levels remain unclear. Here, this study investigated the changes in Rs and microbial metabolic limitation under straw input at four levels (0, 4, 8, and 12 t ha−1 yr−1) based on a long-term (11-year) field experiment. In addition, the C use efficiency (CUE) and C degradation genes were quantified via an enzyme-based biogeochemical-equilibrium model and high-throughput quantitative PCR-based chip technology, respectively. The results indicated that Rs significantly increased with the amount of straw addition, while its rate of increase dropped when the straw addition amount was greater than 8 t ha−1 yr−1. Interestingly, we also observed an apparent microbial P limitation under straw addition at 0 and 4 t ha−1 yr−1 but a shift to N limitation when the straw addition rate was over 8 t ha−1 yr−1. The shift suggested that Rs changes could be attributed to straw addition leading to soil microbes being increasingly limited by N rather than P. Moreover, straw addition significantly increased microbial biomass, reduced CUE and increased the absolute abundance of genes involved in degrading various organic polymers (e.g., starch, hemicellulose, cellulose, chitin and lignin). Partial least squares path modeling revealed that the variation in Rs was directly attributed to increased microbial biomass and C degradation genes as well as declining CUE, while C degradation genes and CUE were mediated by microbial relative C limitation and N vs. P limitation. This study provides insight into the mechanisms of the Rs response to straw addition by linking the Rs to microbial metabolic limitation, CUE and C degradation genes, highlighting that reducing microbial nutrient limitation by balancing metabolic demand and environmental nutrient supply potentially leads to a higher microbial CUE and lower Rs in agricultural ecosystems. •The rate of increase in Rs dropped when straw addition was greater than 8 t ha−1.•Straw input leads to soil microbes being increasingly limited by N rather than P.•Microbial metabolic limitation mediated CUE and the numbers of C-degrading genes.